Konsentrasi Madu Sebagai Pelapis Pada Penyimpanan Kering Terhadap Daya Tetas Ephipia dan Kelangsungan Hidup Naupli Moina macrocopa - Kinanthi Sajda Tsabita; Ahmad Shofy Mubarak; Nina Nurmalia Dewi (Airlangga University, 2024)
Moina macrocopa is natural feed that commonly found in tropical waters. Ephippia can be stored and hatched at any time. Embryo stability can be protect by controlling the water content through coating technology. Honey solution can be used as a coating that have a osmotic regulation for prevent embryo from drought while ephipia entering the dormant stage. This research aims to determine the effect of concentration on the hatchability of ephipia and the survival of M. macrocopa nauplii. The research method used in this study was experimental with a completely randomised design (CRD) using five treatments and four replications. The results showed that coating ephipia using honey had a significantly different effect on the hatchability of M. macrocopa ephipia (p<0,05). However, the concentration of honey was not significantly different on the survival of M. macrocopa nauplii. Keywords : Ephipia, Honey, Moina macrocopa, Coating